1984
DOI: 10.2165/00003088-198409020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ampicillin and Propylthiouracil Pharmacokinetics in Intestinal Bypass Patients Followed Up to a Year after Operation

Abstract: The pharmacokinetics of ampicillin and prophylthiouracil were studied in 6 and 9 patients, respectively, before and several times up to a year after a shunt operation for extreme obesity. The drugs were given intravenously and orally making it possible to estimate the absolute bioavailability. The bioavailability of propylthiouracil (about 80%) was unchanged by the surgical procedure but the fraction of ampicillin (given as pivampicillin) absorbed decreased from a preoperative value of 109 +/- 44% to 44 +/- 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] In one study, BPD was investigated as the surgical procedure, 31 while two studies investigated BPD-DS, 41,50 six studied SG, [32][33][34]43,44,51 and one included jejunoileostomy. 52…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kampmann et al showed decreased absorption of ampicillin after an intestinal shunt procedure in six patients. [113] In addition, a case report suggested that the absorption of amoxicillin and macrodantin in a pregnant female who had undergone Roux-en-y gastric bypass was reduced. This patient was diagnosed with a urinary tract infection and, despite demonstrated bacterial sensitivity to these antibiotics, she did not improve after treatment.…”
Section: Drug Absorption and Bariatric Surgerymentioning
confidence: 99%
“…Generally unaltered except after intestinal bypass surgery Backman et al (1979) Benedech et al (1984) sorption of hydrochlorothiazide (Backman et al 1979) and ampicillin (Kampman et al 1984). In addition, the systemic availability of digoxin may be reduced (Marcus et al 1976).…”
Section: Absorption Distributionmentioning
confidence: 99%